Pericryptal fibroblast sheath in intestinal metaplasia and gastric carcinoma. Issue 1 (10th December 2004) - Mutoh, H; Sakurai, S; Satoh, K; Osawa, H; Tomiyama, T; Kita, H; Yoshida, T; Tamada, K; Yamamoto, H; Isoda, N; Ido, K; Sugano, K
Abstract : Background and aims: In the progression of chronic gastritis, gastric mucosal cells deviate from the normal pathway of gastric differentiation to an intestinal phenotype which is closely related to gastric carcinoma. However, to date, it has not been elucidated whether the intestinal metaplasia is merely a change in the epithelium or whether the underlying mesenchyme also changes from gastric type to intestinal type. We have investigated the relationship between intestinal metaplasia and the pericryptal fibroblast sheath (PCFS) in the mesenchyme. In addition, we also examined PCFS in gastric carcinoma. Methods: We determined the existence of PCFS in the intestinal metaplastic mucosa and carcinoma of both human and Cdx2 transgenic mouse stomach. PCFS was determined using the antibody against α-smooth muscle actin and electron microscopic observations. Results: PCFS formed an almost complete layer around the small and large intestinal crypts while it did not exist around the normal gastric glands in both mice and humans. PCFS was seen around the glands of intestinal metaplastic mucosa in both Cdx2 transgenic mouse and human stomachs. However, PCFS was virtually absent in the intestinal-type gastric adenocarcinoma area. Conclusion: We successfully demonstrated that the epithelium as well as the mesenchyme changed from the gastric type to the intestinal type in intestinal metaplasia and that PCFS disappeared in intestinal-type gastric carcinoma.